Digital Learning, Self-Regulation, and Academic Well-Being Among University Students: A Cyberpsychology Perspective - Diana Devi; Maryanti Maryanti; Suhaibah Suhaibah; Nazira Nazira (ITScience (Information Technology and Science), 2026)
The rapid adoption of digital learning has transformed higher education by increasing learning flexibility while creating psychological challenges, including reduced self-regulation, digital distraction, academic stress, and decreased academic well-being. Despite growing interest in digital learning, limited studies have examined the relationship between self-regulated learning and academic well-being from a cyberpsychology perspective among Indonesian university students. This study aimed to examine the influence of digital learning on students' self-regulated learning and academic well-being and to identify students' psychological profiles within digital learning environments. A quantitative cross-sectional survey was conducted among university students from several higher education institutions in Aceh who actively participated in digital learning through Learning Management Systems and other online platforms. Data were collected using standardized questionnaires and analyzed using descriptive statistics, multiple regression, and cluster analysis. Digital learning significantly predicted self-regulated learning and academic well-being. Students with stronger self-regulation demonstrated higher academic well-being, greater learning autonomy, and better adaptation to digital learning. Cluster analysis further identified distinct psychological profiles, reflecting differences in students' learning management and psychological adjustment. Effective digital learning is closely associated with enhanced self-regulated learning, which contributes to improved academic well-being. These findings emphasize the importance of integrating cyberpsychology principles into higher education to support students' psychological resilience and sustainable digital learning.